The Presence or Absence of Intestinal Microbiota Affects Lipid Deposition and Related Genes Expression in Zebrafish (Danio rerio) - Sheng, Yi; Ren, Hui; Limbu, Samwel M.; Sun, Yuhong; Qiao, Fang; Zhai, Wanying; Du, Zhen-Yu; Zhang, Meiling (Frontiers in Microbiology, 2018)
Understanding how intestinal microbiota alters energy homeostasis and lipid metabolism is a critical process in energy balance and health. However, the exact role of intestinal microbiota in the regulation of lipid metabolism in fish remains unclear. Here we used two zebrafish models (germ-free and antibiotics treated zebrafish) to identify the role of intestinal microbiota in lipid metabolism. Conventional and germ-free zebrafish larvae were fed with egg yolk. Transmission electron microscopy (TEM) was used to detect the presence of lipid droplets in the intestinal epithelium. The results showed that, microbiota increased lipid accumulation in the intestinal epithelium. The mRNA sequencing technology was used to assess genes expression level. We found majority of the differentially expressed genes (DEG) were related to lipid metabolism. Due to the limitation of germ-free zebrafish larvae, antibiotics treated zebrafish were also used to identify the relationship between the gut microbiota and host lipid metabolism. Oil- red staining showed antibiotics-treated zebrafish had less intestinal lipid accumulation than control group. The mRNA expression of genes related to lipid metabolism in liver and intestine were also quantified by using real-time PCR. The results indicated that, Apoa4, hsl, cox15, slc2a1a and lss were more related to intestinal bacteria in fish, while the influence of intestinal microbiota on the activity of fabp6, ascl5, cd36 and gpat2 were different between the liver and intestine. This study identified several genes regulated by intestinal microbiota. Furthermore, the advantages and disadvantages of each model have been discussed. This study provides valuable information for exploring host-microbiota interactions in zebrafish in future.